Structure and zonation of algal turf communities on the Azores: a numerical approach. - Neto, Ana I. (1995)
An appraisal of benthic marine algal communities of the Monte da Guia marine natural reserve (Faial) was undertaken as part of "Expedição Açores 1989". The first account of the subtidal algal communities and zonation for the Azores archipelago by direct observations using SCUBA is presented. In the field quadrats were sampled at intervals along five transects from the littoral fringe to deep subllitoral levels. Intertidal zonation varied according to wave-exposure; some shores were barnacle-dominated but at lower levels much of the vegetation was characterised by a dense algal turf externally uniform in appearance and comprising principally articulated Corallinaceae, together with filiform Chlorophyta, Phaeophyta and Rhodophyta. It extended to at least 30 m depth and there was little variation in species composition and abundance with shore level and continuity into the shallow subllitoral. Numerical methods (Decorana) provided the best means of comparing samples in order to assess similarities and diferences.